(untitled) (Eurasian Journal of Learning and Academic Teaching, 2025)
This article analyzes the theoretical foundations and approaches to developing students’ creativity in vocational education institutions. Based on scientific sources, the concept of creativity is clarified, and the research conducted by Uzbek and foreign scholars is reviewed. The role of interactive methods, digital technologies, and individualized approaches in fostering creativity is highlighted. The article also offers effective methodological recommendations to enhance students’ professional creativity.